Nutritional Status of Kindergarten Children in Medan Helvetia Subdistrict and the Factors Affecting It - Pasaribu, Ira Nurhasanah; Wijaya, Hendri; Sinaga, Bintang Yinke Magdalena; Yunita, Rina (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background: During childhood, especially from toddlerhood to school age, children experience significant body growth. Therefore, children require an adequate concentration of nutrients per kilogram of body weight. Low nutritional status affects the quality of human resources because it affects intelligence and resistance to disease. The aim of the study was to analyse the factors that contribute to the nutritional status of kindergartens in Medan Helvetia Sub-district. Methods. This study was a quantitative analytic study using a cross sectional approach. The study population was kindergartens in Medan Helvetia Subdistrict with a sample of 100 people. The sampling technique in this study used a stratified random sampling method. Data collection method was questionnaire method using questionnaire and 24-hour food recall and anthropometric measurement using weighing tool and microtoise. Data analysis using chi square and fisher’s exact test. Results. Of 100 children, it was known that 58 was female, 42 children was male, 29 children was < 60 months old, 64 children was 60 to 72 months old, 7 children is > 72 months old. 1 child has poor nutritional status, 29 children was found with malnutrition, 57 had good nutritional status, 9 had an overnutrition status, while 4 children was obese. Bivariate analysis of food intake with a p value = 0.004; family income with a p value = 0.672; maternal insight with a p value = 0.234; infectious diseases with a p value = 0.030; immunization status with a p value = 0.399; maternal education level with a p value = 0.092. Conclusion. Factors that influence the nutritional status of kindergarten children in Medan Helvetia Sub-district are food intake and infectious diseases.